2016
DOI: 10.1002/etc.3235
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and food concentration have limited influence on the mixture toxicity of copper and Microcystis aeruginosa to Daphnia magna

Abstract: Standard ecotoxicity tests are conducted under constant and favorable experimental conditions. In natural communities, however, the toxicity of chemicals may be influenced by abiotic and biotic environmental factors. Firstly, the authors examined the influence of temperature and total food concentration on the nature of the combined effects of copper (Cu) and the cyanobacterium Microcystis aeruginosa to Daphnia magna (i.e., whether the combined effects deviated from noninteraction). Secondly, the authors inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…We suggest 3 possible explanations. First, it has already been shown that extreme eutrophication can be unfavorable for most zooplankton species, primarily due to the occurrence of unfavorable cyanobacterial booms (McKee et al 2002), and it is possible that these cyanobacterial booms (e.g., toxins or nutritional quality) affected Zn toxicity (which has, for example, already been shown for Cu; Hochmuth et al 2015). Second, P can also affect certain aspects of the geochemistry of the water.…”
Section: Interactions Of Temperature and P Stress With Zn Toxicitymentioning
confidence: 99%
“…We suggest 3 possible explanations. First, it has already been shown that extreme eutrophication can be unfavorable for most zooplankton species, primarily due to the occurrence of unfavorable cyanobacterial booms (McKee et al 2002), and it is possible that these cyanobacterial booms (e.g., toxins or nutritional quality) affected Zn toxicity (which has, for example, already been shown for Cu; Hochmuth et al 2015). Second, P can also affect certain aspects of the geochemistry of the water.…”
Section: Interactions Of Temperature and P Stress With Zn Toxicitymentioning
confidence: 99%